Edukasi Melalui Plang Uraian Sampah Di Rt 23 Rw 04 Pematang Gubernur - Iqbal, Iqbal; Ripaldo, Ripaldo; Dewi, Dewi; Ahmad, Ahmad; Aldo, Aldo; Putra, Dwingki Marta; Margaretha, Lydia; Mujiono, Mujiono (Jurnal Kewirausahaan & Inovasi, 2026)
This Thematic Student Community Service (KKNT) program focuses on enhancing the ecological awareness of the community in RT 23 RW 04, Pematang Gubernur Village, regarding household waste management. The lack of understanding of the long-term impact of inorganic waste is the primary urgency for conducting this educational intervention. The method applied is based on participatory empowerment, which includes field observations, dialogues with local neighborhood leaders, and the installation of educational signs containing scientific information on waste decomposition time. The results of this service show that the use of static visual media in public spaces effectively stimulates residents to be more prudent in managing waste. This initiative has successfully transformed the community's mindset in perceiving the urgency of environmental cleanliness as a collective responsibility for the sustainability of the local ecosystem.